The Impact of the Covid-19 Pandemic on the Physical Activity Level of the Elderly at the Health Center - boy, Elman boy; Indrisefani, Risfa; Fadhilah, Rahmi; Adityas, Rizky; Fortuna, Jelita; Maulana, Arman; Kurniawan, Sigit; pangaribuan, Danty mandasari; Rianingsih, Rika; prasetyo, Anggi; harahap, Indah putri (Universitas Muhammadiyah Semarang, 2022)
Backgrounds: Due to the COVID-19 cases that emerged in Indonesia, the government issued a regulation on community activity restrictions called the Enforcement of Community Activity Restrictions (PPKM). This PPKM rule causes the temporary cessation of services for the Chronic Disease Management Program (Prolanis) at the puskesmas such as prolanis gymnastics activities.As a result, it has a negative impact on the elderly, namely a decrease in physical activity behavior.Objectives:To assess the level of physical activity of the elderly based on age and gender during the COVID-19 pandemic.Methods:This study uses a non-experimental descriptive research design with a cross-sectional approach. Data collection has been obtained through the International Physical Activity Quitionaire-Short Form (IPAQ-SF). The analytical test that has been carried out is using the chi square test.Results:The results of the study reported that around 59.6% of the elderly experienced light physical activity during Covid-19. This shows that the elderly experienced a decrease in physical activity during the Covid-19 period.Conclusion:The Covid-19 pandemic causes the elderly to behave sedentarily and there is no difference in the level of physical activity in the age group and gender of Prolanis participants at the puskesmas.This study found a decrease in physical activity during the Covid-19 pandemic compared to physical activity before the Covid-19 pandemic.